2004
DOI: 10.1063/1.1828222
|View full text |Cite
|
Sign up to set email alerts
|

Subnanosecond magnetization reversal in magnetic nanopillars by spin angular momentum transfer

Abstract: Sub-ns magnetization switching has been triggered by spin momentum transfer in pulsed current in pillar shaped CoFe∕Cu∕CoFe trilayers. By analyzing the change in magneto-resistance induced after the application of individual short current pulses (100ps–10ns), we measured the probability of magnetization reversal as a function of the current pulse magnitude, polarity and duration, at various temperatures between 150 and 300K. At all studied temperatures, the reversal process can take place within a few 100ps. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
44
4

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 15 publications
3
44
4
Order By: Relevance
“…In contrast with previous measurements where the spin torque is applied throughout a large fraction of a precession cycle, [14][15][16][17][18] in our experiments the magnetization evolves freely except for short time intervals when it is driven by the spin torque. By using ultrashort spin torque "impulses," we can access a previously unexplored regime in which nanomagnet dynamics is strongly affected by the timing of the spin torque pulses with respect to the underlying free precession orbits.…”
mentioning
confidence: 57%
“…In contrast with previous measurements where the spin torque is applied throughout a large fraction of a precession cycle, [14][15][16][17][18] in our experiments the magnetization evolves freely except for short time intervals when it is driven by the spin torque. By using ultrashort spin torque "impulses," we can access a previously unexplored regime in which nanomagnet dynamics is strongly affected by the timing of the spin torque pulses with respect to the underlying free precession orbits.…”
mentioning
confidence: 57%
“…STT can also simply switch the magnetization of a uniaxial nanomagnet [7], which is considered as a promising route for memory applications [8], since this type of switching has proven deep sub-ns potential [9,10]. However, previous investigations have concluded that the reversal speed in the sub-ns regime has insufficient reproducibility.…”
Section: /13mentioning
confidence: 99%
“…Fast pulsed-current reversal experiments have previously been performed 3,4,5,6,7,8 on current-perpendicular-to-the-plane (CPP) spin valve devices in which both the polarizing fixed magnetic layer and the switchable free magnetic layer have moments that lie in the sample plane in equilibrium (see Fig. 1b inset).…”
mentioning
confidence: 99%